Effectiveness of silicone gel combined with pressure garment for prevention of post-burn hypertrophic scar: A randomized controlled trial - P. Muangman (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2020. Background: The objective of post-burn hypertrophic scar prevention is to improve patient quality of life. Many treatments have been employed to obviate hypertrophic scarring, but the optimal treatment has not yet been identified. Several studies have demonstrated the potential of silicone gel in scar prevention. Objective: To investigate the efficacy of silicone gel combined with pressure garment for prevention of post-burn hypertrophic scar. Materials and Methods: This randomized controlled trial included patients with completely epithelialized post-burn wound injury that were recruited from the Burn Unit of the Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand. Study patients were allocated to the pressure garment alone group (control) or the pressure garment with silicone gel group (study). Gel was applied to scar tissue twice daily after bathing, and the pressure garment was worn for 23 hours each day for 24 weeks. Scars were evaluated using the Vancouver Scar Scale (VSS) at 2, 4, 12, and 24 weeks of treatment. Results: Fifty patients (25 per group) were included. The average age of patients and size of wound was 39.74+10.75 years and 95.95+29.30 cm2, respectively. Most patients (72%) were male. There was no significant difference between groups for age, gender, size of burn wound, or infection. The study group demonstrated significantly lower pigmentation (at week 24, p<0.05), increased pliability (at weeks 12 and 24, p<0.05), and decreased height (at week 24, p<0.05) than the control group; however, no significant difference was observed between groups for vascularity, pain, or itching. Total modified VSS score was significantly lower in the study group than in the control group at 12 and 24 weeks (p<0.05). Conclusion: The present study demonstrated the statistically significant benefit of combining silicone gel with pressure garment for post-burn hypertrophic scar prevention compared to pressure garment alone.